125k views
5 votes
Solve -1/6 (3x – 9) – 9= 3.

The solution is x=

Please explain

User Sebt
by
4.8k points

1 Answer

2 votes

Answer:

x=23

Explanation:

1/6 as a decimal is 0.16666667 but i rounded it to 0.2

so the equation is the 0.2(3x-9)-9=3

then i did 0.2 times 3x =0.6x

then 0.2 times -9= -1.8

so the equation now looks like this:

0.6x-1.8x-9=3

so i add 1.8 and 9 to 3 which gives you 13.8

then the equation looks like this:

0.6x=13.8

then you do 13.8 divided by 0.6 which equals 23.

hope this helps

tell me if i got it right or wrong

User Kallen
by
4.7k points